Road traffic injury prevention in Malaysia: Research and practice - Bhuiyan, Munira; Bhuiyan, Moinul (2012)
Road traffic injuries (RTIs) are a major cause of mortality, morbidity and disability in Malaysia contributing more than 23 per 100,000 people die and additional 71 per 100,000 people are injured or disabled every year. Though the upward trend of RTIs dropped slowly but the road traffic deaths have been increasing from 2,303 in 1974 to 6,872 in 2010. This article is an attempt to review the current impact of road safety initiatives carried out by the Malaysian Government and other organizations through published literature.